2020
DOI: 10.1097/meg.0000000000001794
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of liver stiffness-based risk prediction model during antiviral therapy in patients with chronic hepatitis B

Abstract: Objective The liver stiffness-based risk prediction models predict hepatocellular carcinoma (HCC) development. We investigated the influence of antiviral therapy (AVT) on liver stiffness-based risk prediction model in patients with chronic hepatitis B (CHB). Methods Patients with CHB who initiated AVT were retrospectively recruited from 13 referral Korean institutes. The modified risk estimation for hepatocellular carcinoma in chronic hepatitis B (mREAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Oral NUC therapy was initiated on the basis of both the practice guideline by the Korean Association for the Study of the Liver 23 and the reimbursement guideline by the national health insurance service of the ROK (Table ). LS was measured using TE (FibroScan ® , EchoSens, Paris, France) in a standard manner 21,24 . Cirrhosis on ultrasonography was defined when at least one of the following criteria was fulfilled; irregular‐nodular liver surface, highly coarse liver echo‐texture, blunt liver edge, shrunken liver parenchyme, disturbed or destroyed vascular architecture, and other findings suggestive of portal hypertension such as splenomegaly (>12 cm) or porto‐systemic collaterals 25–30 …”
Section: Methodsmentioning
confidence: 99%
“…Oral NUC therapy was initiated on the basis of both the practice guideline by the Korean Association for the Study of the Liver 23 and the reimbursement guideline by the national health insurance service of the ROK (Table ). LS was measured using TE (FibroScan ® , EchoSens, Paris, France) in a standard manner 21,24 . Cirrhosis on ultrasonography was defined when at least one of the following criteria was fulfilled; irregular‐nodular liver surface, highly coarse liver echo‐texture, blunt liver edge, shrunken liver parenchyme, disturbed or destroyed vascular architecture, and other findings suggestive of portal hypertension such as splenomegaly (>12 cm) or porto‐systemic collaterals 25–30 …”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, other HCC prediction models using fibrosis parameters assessed during long-term AVT (i.e., modified REACH-B, CAGE-B, and SAGE-B scores) have also been introduced with promising results [16,17]. Most recently, given that baseline fibrosis and/or necro-inflammation can be partially modified or regressed through long-term AVT [18][19][20], Nam et al [21] recently suggested a novel HCC prediction model using fibrosis markers assessed at dual time points, named the Fibrosis marker response, Sex, Age, and Cirrhosis (FSAC) score. The model incorporates on-therapy changes, including a fibrosis index based on four factors (FIB-4) [22,23] and aspartate aminotransferase (AST)-to-platelet ratio index (APRI) [24] at 12 months, as well as sex, age, and cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, parameters reflecting fibrotic burden, such as serum fibrosis markers, ultrasonography findings, and LS, have been always crucial components. Given that such indices can change dynamically through fibrosis regression during prolonged potent AVT, 37 we aimed to identify an optimal cutoff for on-treatment LS for more accurate prognostication and to compare its usefulness to that of gross ultrasonography findings or other LS cutoffs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although LS may not perfectly reflect the degree of change in histological fibrosis, the gold standard for predicting prognosis in chronic liver diseases, among CHB patients receiving prolonged AVT, LS remains the most widely validated tool by which clinically relevant information can be obtained easily and non-invasively in real-life practice. Third, from a practical viewpoint, we selected the time point of ≥2 years of AVT to re-assess the risk of HCC based on the study by Chon et al 37 which indicated significant dynamic changes in HCC risk scores occur for up to 2 ~ 3 years after AVT initiation. In contrast, Papatheodoridis et al 24 focused on patients who had been receiving potent AVT for at least 5 years.…”
Section: Discussionmentioning
confidence: 99%